Relationship between wheat flour properties and french bread char- acteristics using principal component analysis - Gallardo, Anabella Elisabet (2015)
The objective was to use Principal Component Analysis as a tool to assess the relationship between physical and rheological characteristics of wheat flour and the quality of french bread. Flours belonging to eight varieties of Argentine commercial wheats (Triticum aestivum L.) were studied. Physical and chemical determinations were performed on grains and then milled to obtain experimental flours. The rheological behaviour of flours was analysed through the alveographic and farinographic parameters and the technological characteristics through the French bread making. Principal component analysis was used as a statistical tool. The three principal components used can explain 78.4% of the variability of the original data extracted. Through the found results a certain association between alveographic and farinograph parameters was obtained, but were not found a close relationship between these physical properties with the specific volume of bread. So the PCA seem not to be an optimal tool to predict the quality of French bread from the properties of wheat flour. Nevertheless, the baking test appears as the more accurate tool to assess globally the parameters that determine the quality of flour.